Tourism economic resilience and its influence factors in China’s three major urban agglomerations based on threshold effect - yelin fang; jiatong huang; zhenfang huang; yunhan li (Humanities & Social Sciences Communications)
Abstract Tourism economic resilience relates to the theme of high-quality tourism development. Based on the relevant data of the three major urban agglomerations in eastern China from 2009 to 2020, this study measures the economic resilience of tourism. It analyzes the impact factors of threshold variables. The findings are as follows: Tourism economic resilience in the three major urban agglomerations exhibits an “inverted V-shaped” trend, with significant disparities in resilience level among different cities. Tourism economic resilience in the three major urban agglomerations shows an imbalance in space. In the Beijing-Tianjin-Hebei and Pearl River Delta urban agglomerations, large cities exhibit relatively high resilience. The value of eastern cities in the Yangtze River Delta urban agglomeration is higher than that of the west. Economic development level (EDL), informatization level (IL) and government intervention (GI) have significant threshold effects on tourism economic resilience. Under different threshold variables, the impact on tourism economic resilience is quite different. Urbanization levels and infrastructure improvements have a significant positive impact on tourism economic resilience. Relevant countermeasures and suggestions are proposed to improve tourism economic resilience.